Nursing student caring behaviours: a systematic review - Permana, Bhakti; Yusuf, Ah.; Bakar, Abu (International Journal of Public Health Science (IJPHS), 2024)
Caring is central to nursing and requires scientific professional skills and knowledge. Numerous definitions highlight the fact that there is a range of perspectives regarding the caring behaviors. The purpose of this study was to provide a summary of caring behaviors among nursing students in order to depict a more comprehensive view, which could be used as foundational data for the argument that cultivating caring behaviors should be an early focus of the nursing curriculum. Article selection was guided by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) Statements. Literature searches were conducted in June 21, 2022 in PubMed, cumulative index to nursing and allied health (CINAHL), and (OVID). The following search blocks were generated: nursing students, caring behavior, and education. About 318 were found using primary search descriptors and 19 studies were included in the review. All research was published between 2016 and 2020. The majority of studies were conducted using a cross-sectional design, two studies used prospective, and one study used a retrospective design. The caring behavior of nursing students varies depending on the country and instrument used, ranging from a moderate score to a high score, and varies from one study year to the next. The most dominant caring behavior domains reported are the domains of instrumental caring/physical caring and expressive caring/emotional caring. This study adds to the existing literature on nursing care and explains the universality of the concept of care from multiple theoretical perspectives. Caring interventions should be used to help students develop clinically-relevant caring behaviors.